DOCKING STUDIES OF SUBSTITUTED CHROMAN ANALOGS AT ESTROGEN RECEPTOR - Rawat, Pinki; Verma, Saurabh Manaswita (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The objective of the present study is to perform the molecular docking studies of some newly designed chroman analogs on estrogen receptor (ER) (PDB: 1YIM) by Glide v5.0. Methods: The docking studies of designed chroman analogs were performed on the active site of ER (PDB: 1YIM) for anti-breast cancer activity using Schrodinger Glide v5.0. Absorption, distribution, metabolism, excretion properties of all designed compounds were also calculated by Qik Prop v3. 0. Results: Among all compounds, compound 38 showed highest docking score (âˆ’8.17) in the series. Docking scores were compared with standard drugs tamoxifene (âˆ’11.08) and anastrazole (âˆ’7.86). All compounds were found to be within expectable range for percent human oral absorption, octanol/water partition coefficient (QP log Po/w), brain/blood partition coefficient (QP log BB), total solvent accessible surface area, and rule of five predicted by Qikprop. Conclusion: Most of the compounds in the series showed good molecular docking score on the ER (PDB: 1YIM). Compound 38 (âˆ’8.16) exhibited better docking score than standard drug anastrazole (âˆ’7.86). Most of the pharmacokinetic properties conducted by Qikprop were found to be within the permissible range. Keywords: Chroman, Docking, Estrogen receptor, Lipinski’s rule of five.